Molecular cloning, characterization and expression analysis of caspase-3 from the oriental river prawn, Macrobrachium nipponense when exposed to acute hypoxia and reoxygenation. Issue 62 (March 2017) - Sun, Shengming; Xuan, Fujun; Fu, Hongtuo; Zhu, Jian; Ge, Xianping; Wu, Xugan
Abstract: Caspases are present in the cytosol as inactive proenzymes but become activated when apoptosis is initiated, playing an essential role at various stages of the process. In this study, a caspase-3 (Mncaspase-3c) was cloned from gill of the oriental river prawn Macrobrachium nipponense by reverse-transcription polymerase chain reaction and rapid amplification of cDNA ends, and its properties were characterized. The 1730-bp cDNA contained an open reading frame of 1566 bp, a 123-bp 5′-untranslated region (UTR), and a 41-bp 3′-UTR containing a poly(A) tail. The molecular mass of the deduced amino acid (aa) sequence (521 aa) was 56.3 kDa with an estimated pI of 5.01. The MnCaspase-3c sequence contained a predicted caspase family p20 domain and a caspase family p10 domain at positions 236–367 and 378–468 respectively. Recombinant MnCaspase-3c protein was expressed in Escherichia coli and purified. In vitro activity assays indicated that the recombinant MnCaspase-3c hydrolyzed the substrate Ac-DEVD-pNA, suggesting a physiological role as a caspase-3. Caspase-3c gene transcripts were distributed in all M. nipponense tissues tested by quantitative RT-PCR, being especially abundant in hemocytes. Comet assays in gill tissues showed an obvious time-dependent response to hypoxia. Furthermore, Mncaspase-3c, at both the mRNA and protein levels, was demonstrated to participate in the apoptotic process in gill after stimulation by acute hypoxia. Overall, these results indicate that hypoxia triggers apoptosis in shrimp gill tissues. Highlights: A capspase-3 like protein was identified in river prawn Macrobrachium nipponense . Recombinant MnCaspase-3c hydrolyzed the substrate Ac-DEVD-pNA. Mncaspase-3c participated in apoptosis in gills associated with oxidative stress after stimulation by acute hypoxia.